The Dynamics of Thought - Gardenfors, Peter (Synthese Library, Studies in Epistemology, Logic, Methodology, and Philosophy of Science, 2005)
This volume is a collection of some of the most important philosophical papers by Peter Gärdenfors. Spanning a period of more than 20 years of his research, they cover a wide ground of topics, from early works on decision theory, belief revision and nonmonotonic logic to more recent work on conceptual spaces, inductive reasoning, semantics and the evolutions of thinking. Many of the papers have only been published in places that are difficult to access. The common theme of all the papers is the dynamics of thought. Several of the papers have become minor classics and the volume bears witness of the wide scope of Gärdenfors' research and of his crisp and often witty style of writing. The volume will be of interest to researchers in philosophy and other cognitive sciences.